Mountain tourism facing climate change. Assessing risks and opportunities in the Italian Alps - Pede, Elena Camilla; Barbato, Giuliana; Buffa, Alessandra; Ellena, Marta; Mercogliano, Paola; Ricciardi, Guglielmo; Staricco, Luca (TeMA - Journal of Land Use, Mobility and Environment, 2022)
The Alps are an interesting case for studying the relationship between tourism and climate change. Despite a growing number of studies, the climate change impacts on the tourism sector remain uncertain, when the regional and local scale or seasonality are considered. This article presents a risk methodology to assess the spatial distribution of the main challenges and opportunities for winter and summer tourism due to climate change at the sub-regional level on a 2021-2050 scenario. This methodology has been tested on an Italian Alpine area, which consists of very different landscapes from plain to high mountains. The results show that high-altitude municipalities will face the stronger risks for winter touristic activities, due to reduced snow cover duration, but also opportunities to attract in summer tourists escaping from the hotter temperatures of the plain. At the same time, climate change could have secondary negative effects in these areas, as it will increase the frequency and the magnitude of extreme events. The results show that impacts of CC cannot be generalised, even in a limited area; same hazards due to changes in temperature and precipitation patterns can generate very different risk scores, because of local conditions related to exposure and vulnerability factors.